GRANADA: A Generic RAdiative traNsfer AnD non-LTE population algorithm - Funke, B.; López-Puertas, M.; García-Comas, M.; Kaufmann, M.; Höpfner, M.; Stiller, G.P. (Journal of quantitative spectroscopy & radiative transfer, 2012)
We present in this paper the Generic RAdiative traNsfer AnD non-LTE population Algorithm (GRANADA). This model is able to compute non-LTE populations for vibrational, rotational, spin (i.e., NO and OH), and electronic (i.e., O2) states in a given planetary atmosphere. The model is very flexible and can be used for computing very accurate non-LTE populations or for calculating reasonably accurate but at high speed non-LTE populations in order to implement it into non-LTE remote sensing retrievals. We describe the model in detail and present an update of the non-LTE collisional processes and their rate coefficients for the most important molecules in Earth's atmosphere. In addition, we have applied the model to the most important atmospheric infrared emitters including 13 species (H2O, CO2, O3, N2O, CO, CH4, O2, NO, NO2, HNO3, OH, N2, and HCN) and 460 excited vibrational or electronic energy levels. Non-LTE populations for all these energy levels have been calculated for 48 reference atmospheres expanding from the surface up to 200km, including seasonal (January, April, July and October), latitudinal (75°S, 45°S, 10°S, 10°N, 45°N, 75°N) and diurnal (day and night) coverages. The effects of the most recent updates of the non-LTE collisional parameters on the non-LTE populations are briefly described. This climatology is available online to the community and it can be used for estimating non-LTE effects at specific conditions and for testing and validation studies. ► We present the Generic RAdiative traNsfer AnD non-LTE population Algorithm (GRANADA). ► It computes vibration/rotation/spin/electronic populations of planetary atmospheres. ► We update the non-LTE collisional processes and rates for the atmospheric molecules. ► We present a non-LTE climatology for H2O, CO2, O3, N2O, CO, CH4, O2, NO, NO2, HNO3, OH, N2 and HCN.